2002
DOI: 10.1111/j.1553-2712.2002.tb01586.x
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Communication and Interpersonal Skills Competencies

Abstract: Excellent communication and interpersonal (C-IP) skills are a universal requirement for a well-rounded emergency physician. This requirement for C-IP skill excellence is a direct outgrowth of the expectations of our patients and a prerequisite to working in the increasingly complex emergency department environment. Directed education and assessment of C-IP skills are critical components of all emergency medicine (EM) training programs and now are a requirement of the Accreditation Council for Graduate Medical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
60
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(61 citation statements)
references
References 52 publications
0
60
0
1
Order By: Relevance
“…11−13 In our review, we found that establishing and building a therapeutic relationship with patients is a key communication task for physicians, 1−4,7−10 including for the specialty of EM. 5,13,14 Likewise, the demonstration of empathy is important in the patient care encounter. 3,4,8,10,14 However, rapport building is challenging for EM physicians because of time constraints in a busy emergency department (ED); the possibility of a rapidly changing patient status, often of a deteriorating and critical nature; and/or the absence of an established relationship with the patient.…”
Section: Descriptionmentioning
confidence: 99%
See 2 more Smart Citations
“…11−13 In our review, we found that establishing and building a therapeutic relationship with patients is a key communication task for physicians, 1−4,7−10 including for the specialty of EM. 5,13,14 Likewise, the demonstration of empathy is important in the patient care encounter. 3,4,8,10,14 However, rapport building is challenging for EM physicians because of time constraints in a busy emergency department (ED); the possibility of a rapidly changing patient status, often of a deteriorating and critical nature; and/or the absence of an established relationship with the patient.…”
Section: Descriptionmentioning
confidence: 99%
“…3,4,8,10,14 However, rapport building is challenging for EM physicians because of time constraints in a busy emergency department (ED); the possibility of a rapidly changing patient status, often of a deteriorating and critical nature; and/or the absence of an established relationship with the patient. 5,14 We therefore chose to include basic interpersonal skills and empathy in our CIPS curriculum to teach residents how to develop this key physician-patient connection in the ED environment.…”
Section: Descriptionmentioning
confidence: 99%
See 1 more Smart Citation
“…We did not find any instrument that was comprehensive enough to meet all of our learning objectives. Therefore we elected to develop a checklist based on available tools in the literature (Rosenzweig et al 1999;Makoul 2001;Hobgood et al 2002;Residorff et al 2003;Chapman et al 2004;Duffy et al 2004;Kalet et al 2004;Lang et al 2004;CORD 2005;Schirmer et al 2005;Shayne et al 2006). The CIPS checklist we developed consists of 22 behaviorally based skills in one of five categories in which the evaluator notes whether the skill was performed or not (Table 3).…”
Section: Cips Assessmentmentioning
confidence: 99%
“…Our review of the literature on communication and interpersonal skills (CIPS) revealed that much of the communication instruction that medical schools offer does not focus on communication tasks specific, even unique, to caring for the critically ill patient (Makoul 2001;Hobgood et al 2002;Duffy et al 2004;Kalet et al 2004;Lang et al 2004). In addition, the Initiative to Transform Medical Education provided by the American Medical Association (AMA) challenged educators to address the following medical education gaps: the physician's ability to rapidly synthesize information while simultaneously caring for patients, the physician's role as a member of the healthcare team, and the physician's ability to communicate effectively in difficult situations and demonstrate a caring manner (AMA 2007).…”
Section: Introductionmentioning
confidence: 96%